Identifying and tuning coordinated water molecules for efficient electrocatalytic water oxidation - Geng Zhang; Wei Guo; Hong Zheng; Xiang Li; Jinxin Wang; Qiuyu Zhang (Nature Communications)
Abstract Coordination complexes are promising candidates for powerful electrocatalytic oxygen evolution reaction but challenges remain in favoring the kinetics behaviors through local coordination regulation. Herein, by refining the synergy of carboxylate anions and multiconjugated benzimidazole ligands, we tailor a series of well-defined and stable coordination complexes with three-dimensional supramolecular/coordinated structures. The coordinated water as potential open coordination sites can directly become intermediates, while the metal center easily achieves re-coordination with water molecules in the pores to resist lattice oxygen dissolution. In situ experiments and theory simulations indicate that nickel centers with neighboring coordinated water molecules follow an intramolecular oxygen coupling mechanism with a low thermodynamic energy barrier. With more coordinated water introduced, an optimized intramolecular oxygen coupling process may appear for favoring the reaction kinetics. As such, a low overpotential of 248 mV at 10 mA cm–2 and long-term stability of 200 h are achieved. This study underscores the potential of crafting coordinated water molecules for efficient electrocatalysis applications.